Thermochromic Materials for Smart Windows: A State-of-Art Review - Wang, Xuanjie; Narayan, Shankar (Frontiers in Energy Research, 2021)
Smart windows that regulate solar energy by changing optical characteristics have recently gained tremendous interest for energy-saving and indoor-comfort applications. Among them, thermochromic smart windows are promising because of their simplicity for industrial production and ease of implementation. Although significant advancements have been reported on thermochromic materials, both optical and transition properties remain unsatisfactory. This review focuses on the recent advancement of thermochromic materials for smart windows in terms of operation, performance, and potential for commercialization. It discusses the parameters typically used for gauging performance and provides a summary and comparison of various promising thermochromic materials, including vanadium dioxide, hydrogels, and perovskites. The article also points the challenges in the practical implementation of these materials and provides an outlook for future development.